The Development Of M-Learning Lessons Using Cloud Computing-Based Interactive Games To Promote Academic Engagement For Vocational Students - วังปรีชา กิจฎามาศ (Al-HIKMAH Journal, 2021)
The objectives of this research were 1) to develop and determine the efficiency of M-learning lessons by using cloud computing-based interactive games to promote academic engagement in studying for vocational students, 2) to study academic achievement by using M-learning lessons through cloud computing-based interactive games to promote academic engagement in studying for the vocational students, 3) to measure academic engagement of the vocational students after using M-learning lessons through cloud computing-based interactive games, and 4) to study the satisfaction with the developed M-learning lessons through cloud computing-based interactive games of the vocational students. The sample of this study consisted of 30 vocational students in Sukdisilpin Commercial Vocational College. They were selected by purposive sampling for selected class. Research instruments consisted of 1) M-learning lessons through cloud computing-based interactive games, 2) academic achievement test in Computer and Information for Careers course, 3) quality evaluation scale for M-learning lessons, 4) satisfaction assessment scale, and 5) academic engagement scale. Data were analyzed using statistics, including percentage, mean ( ) , standard deviation (S.D.), efficiency index (E1 / E2), index of consistency (IOC), and t-test dependent samples. The results of this research indicated that 1) the developed M-learning lessons by using cloud computing-based interactive games consisted of four components, namely 1. Description Section, 2. M-Learning Management System (MLMS), 3. Content Management System (CMS), and 4. Interaction with Learners. When the quality of the instruments was examined by experts, overall opinion on the developed M-learning lessons was at a good level. 2) The efficiency index (E1/E2) of the developed M-learning lessons was 89.73 / 81.33, which met the specified criteria. 3) Academic achievement of the sample by using M-learning lessons through cloud computing-based interactive games at posttest period was higher than that at pretest period. 4) Overall academic engagement of the sample in Computer and Information for Careers course was at a high, and 5) overall satisfaction of the sample with the developed M-Learning lessons was at the highest level ( =4.63, S.D.= 0.23)